2014
DOI: 10.2478/s11536-013-0241-y
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation and serum susceptibility in Pseudomonas aeruginosa

Abstract: AbstractPseudomonas aeruginosa (P. aeruginosa) is one of the most important opportunistic pathogens. The pathogenicity of P. aeruginosa has been associated with multiple bacterial virulence factors. The aim of this study was to evaluate the association between P. aeruginosa strains obtained from various clinical samples and resistance to antibiotics and pathogenicity factors, such as resistance to serum bactericidal activity and biofilm formation. This study included 121 P. aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In our study, biofilm production was 29.2% from wound, 37.5%from burn, 60.6% from urine and 57.9% from ETA specimens . We didn't find any statistically significant differences in biofilm production among the P. aeruginosa strains recovered from different specimens, which comes in agreement with the result of Mikucionyte et al (18).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, biofilm production was 29.2% from wound, 37.5%from burn, 60.6% from urine and 57.9% from ETA specimens . We didn't find any statistically significant differences in biofilm production among the P. aeruginosa strains recovered from different specimens, which comes in agreement with the result of Mikucionyte et al (18).…”
Section: Discussionsupporting
confidence: 92%
“…They showed that, at early stages of growth, serum can repress the expression of many P. aeruginosa genes, and it can enhance them in the late phase. HF's ability to enhance P. aeruginosa susceptibility to human serum becomes even more important in light of the fact that serum-resistant phenotypes of P. aeruginosa are more frequently isolated from wounds and blood than infections at other sites [54]. Wound infections are believed to occur when microbial burden exceeds the innate clearance capacity of the host immune system [10].…”
Section: Discussionmentioning
confidence: 99%
“…; Mikucionyte et al . ), mainly for microbial strains recovered from blood (Dolan ). It is known that organic components, such as proteins (albumin, fibrinogen, fibronectin and laminin) and platelets, play a key role as matrix determinants important in microbial adhesion and biofilm composition (Dolan ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors attested that bacterial adhesion, aggregation and proliferation in the thin biofilm layer were increased in the presence of serum, leading to an in vitro thick mature biofilm. Serum components may promote biofilm formation (Samaranayake et al 2013;Mikucionyte et al 2014), mainly for microbial strains recovered from blood (Dolan 2002). It is known that organic components, such as proteins (albumin, fibrinogen, fibronectin and laminin) and platelets, play a key role as matrix determinants important in microbial adhesion and biofilm composition (Dolan 2002).…”
Section: Discussionmentioning
confidence: 99%